SIBINAR on increasing midwife competence and independence of pregnant mothers in early detection of pregnancy risk and stunting prevention - Yuliasti Eka Purnamaningrum; Lucky Herawati; Yuni Kusmiyati; Dwiana Estiwidani (Jurnal Kesehatan Ibu dan Anak, 2021)
The competence of midwives and mother's independence in early detection of high-risk pregnancies and prevention of stunting are important factors to improve health status in Indonesia. The purpose of this study was to know the effect of SIBINAR on increasing the competence of midwives and the independence of pregnant women in early detection of pregnancy risk and stunting prevention. This type of research was a quasi-experimental with a pre-test post-test design. The subjects in this study were all midwives and pregnant women in Indonesia. The sampling technique used is accidental sampling. The calculation of the sample size using the formula for the difference in the mean of independent samples. The number of samples of midwives was 80, the number of samples of pregnant women was 30. There was effect of SIBINAR on the improvement of midwife competence in early detection of pregnancy risk (pre-test mean=65.86; post-test mean=80.95; SD=15.09 (11.03); p-value=0.000) and stunting prevention (pre-test mean=60.44; post-test mean=1.53; SD=31.09 (11.03); p-value=0.000). There was effect of SIBINAR on independence of pregnant women in early detection of pregnancy risk (pre-test mean=79.5; post-test mean=99.06; SD=19.48 (54.3); p-value=0.000) and stunting prevention (pre-test mean=67.86; post-test mean=3.82; SD=5.96 (15.5); p-value=0.000). There is an effect of SIBINAR on increasing the competence of midwives in early detection of pregnancy risk and stunting prevention and there is an effect of SIBINAR on pregnant women's independence in early detection of pregnancy risk and stunting prevention.